THE ROLE OF MEDAN GENERASI BERENCANA (GENRE) AMBASSADOR INCREASING KNOWLEDGE OF ANEMIA AND FREE SEX ON PEERS (British Journal of Global Ecology and Sustainable Development, 2023)
The success and success of a nation in the future is determined by the quality of adolescents today, this is the basis why adolescents need mendapatkan special attention and assistance khususin all aspects of their lives. Adolescent life should be prepared as early as possible in order to create adolescents who have optimal quality that is healthy physically, spiritually, mentally, socially and spiritually.